Legal Standing Of Branch Offices Of A Limited Company - Nadila Manda Sari; Annisa Nurul Husna; Salsabila Yasmin; Rafinsyah Adhimulya Himawan; Mirza Fuqaha Sayyidin Ganing (LEGAL BRIEF, 2022)
In creating a Limited Liability Company in Indonesia, the founder of the company seek to use economic principles as much as possible, one of which is opening a location close to raw materials, labor, or consumer markets in order to broaden the scope of their operations. As a result, the head office created branch offices in several areas. This study seeks to determine the legal standing of a limited company's branch offices. The branch office is directly accountable to the head office, hence the head office is responsible for all actions and legal consequences that result. In that instance, the legal standing of the branch office will follow that of the main office, and the branch office will not be able to stand on its own legally.